Perancangan Meja Laptop Portable untuk Mahasiswa Teknik Industri Universitas Singaperbangsa Karawang - Herwanto, Dene; Gumelar, Anwar Jaya; Aolia, Saeful (Performa: Media Ilmiah Teknik Industri, 2015)
Laptop has now become a necessity for students of Industrial Engineering of Unsika. Unfortunately, they use a laptop in a bad way, where they sit on the floor and put the laptop on the lap. This can cause a variety of health problems, such as neck pain, hot legs, back pain, and even humpback. To overcome those problems, we need a portable laptop table, that making it easy to carry, stored, and transported. Currently, the market has circulated many types of portable laptop table, but still less appropriate for students of Industrial Engineering of Unsika. This research aims to design a portable laptop table suitable for students of Industrial Engineering of Unsika. From the research, the results showed that this laptop table is made from PVC pipe, knock-down with a height 244 mm, width 444 mm, length 305 mm, and height of under table at least 211 mm